Biological characteristics of the Pleurotus cultivars in southwestern Viet Nam - Ho, B. T. Q.; Huynh, N. M. T.; Co, D. T.; Dinh, M. H.; Pham, N. D. H. (International Journal of Agricultural Technology, 2022)
The biological characteristics of Pleurotus cultivars in the southwestern region of Viet Nam were conducted by morphology, molecular phylogeny, spawn running and biological efficiency. Total 10 Pleurotus cultivars were belonged to 5 morphotypes as following: 5 cultivars GTG1, GBT1, GBT2, GVL1, GVL3 belonged to phoenix type, 2 cultivars WSG1, WVL1 belonged to oyster type, a cultivar YVL1 belonged to golden oyster type, a cultivar PVL1 belonged to pink oyster type, and a cultivar DgSG1 belonged to blue oyster type. By morphological and phylogenetic analysis, all 5 phoenix cultivars were identified to P. pulmonarius, both 2 oyster cultivars and a blue oyster cultivar were P. ostreatus, a golden oyster cultivar was P. citrinopileatus, and a pink oyster cultivar was P. djamor. By the model of 1.2 kg rubber tree sawdust in nylon bag, the spawn running of golden oyster cultivar (12.47±1.20 mm/day) and pink oyster cultivar (11.29±1.00 mm/day) was higher than all phoenix cultivars, and the spawn running of blue oyster cultivar was lowest (6.57±0.76 mm/day). The biological efficiency in conventional production of oyster cultivars was highest (37.58±5.00% of WSG1 and 34.84±3.90 of WVL1), opposite to blue oyster cultivar was lowest (12.93±3.93%). This the first study described the macro and micro morphological characteristic of commercial mushroom cultivars in Viet Nam. Combining the molecular and morphological identification, all these cultivars could be used as the parent in crossing due to their putative strain and standard characteristic of species. The results of cultivation under a standardized conditions should be a value data to screen and breed the new cultivar